If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4y + 3) = 6 Reorder the terms: 2(3 + 4y) = 6 (3 * 2 + 4y * 2) = 6 (6 + 8y) = 6 Add '-6' to each side of the equation. 6 + -6 + 8y = 6 + -6 Combine like terms: 6 + -6 = 0 0 + 8y = 6 + -6 8y = 6 + -6 Combine like terms: 6 + -6 = 0 8y = 0 Solving 8y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '8'. y = 0 Simplifying y = 0
| 9x-95=38+2x | | 2x+67=6x+7 | | .40x+.60y=24 | | 3yd=12y | | 7(2x-2)=-126 | | 5x+10+7x+50=180 | | -31+2x=-5(4x-7) | | 2x-5y=14fory | | 5x+10+7x+50= | | 9x-4=2r+3 | | 7x(5x+10)=x | | 8-7x-2=-15+4x-12 | | 7x+3=10x-45 | | -5t+7=11t+-25 | | 3x-5=-5-2x | | -8x+5=23 | | (16+2x)X(12+2x)=320 | | 7x(5x+10)=7x | | 4(4-4k)=-10-16 | | 16x-8=36 | | 1x+-4+2x=14 | | 10v-3-v=0 | | -2t^2+8t+1=0 | | -5t+7=11+-25 | | 4x+x+5=54 | | 8x^2y+8y=2x | | -9k+10-8k=0 | | -.250y+2=0 | | 180=(7x-3)(12x-7) | | 7-6x=-23 | | 2x-9=1-3x | | 5(x+10)=7x |